The role of marketing in combating covid-19 in ghana; traditional marketing versus social marketing - OMAN FAUSTINA MAMLE (KNUST, 2024)
A thesis submitted to the department of marketing and corporate strategy of the school of business, Kwame Nkrumah university of science and technology, Kumasi in partial fulfilment of the requirements for the degree of master of science in marketing